2020
DOI: 10.1523/jneurosci.1397-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Memory Load Alters Perception-Related Neural Oscillations during Multisensory Integration

Abstract: Integrating information across different senses is a central feature of human perception. Previous research suggests that multisensory integration is shaped by a context-dependent and largely adaptive interplay between stimulus-driven bottom-up and top-down endogenous influences. One critical question concerns the extent to which this interplay is sensitive to the amount of available cognitive resources. In the present study, we investigated the influence of limited cognitive resources on audiovisual integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…This difference was only present in the older group. In audiovisual stimuli, an increase in theta power has been linked to incongruence processing and the need for cognitive control to successfully enable audiovisual integration (Michail et al, 2021 using the sound induced flash illusion; Morís Fernández et al, 2015 using McGurk stimuli). At the time of sound onset, the preceding visual information is already partially processed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference was only present in the older group. In audiovisual stimuli, an increase in theta power has been linked to incongruence processing and the need for cognitive control to successfully enable audiovisual integration (Michail et al, 2021 using the sound induced flash illusion; Morís Fernández et al, 2015 using McGurk stimuli). At the time of sound onset, the preceding visual information is already partially processed.…”
Section: Discussionmentioning
confidence: 99%
“…Midfrontal theta (4-8 Hz) is thought to reflect communication between different brain areas when the need for cognitive control arises (Cavanagh & Frank, 2014). An increase in theta power can be observed in tasks with high working memory load (Gevins, 1997;Jensen & Tesche, 2002;Maurer et al, 2015; for audiovisual speech stimuli Michail et al, 2021). In audiovisual tasks, theta band activity has been attributed to divided attention (Keller et al, 2017) and the encoding of new information and change detection (Fingelkurts et al, 2007).…”
Section: Thetamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, more energy was allocated to the visual stimulus under medium visual perceptual-load conditions than that under low visual perceptual-load conditions, and more under high visual perceptual-load conditions than that under medium visual perceptual-load conditions. Additionally, a recent study reported that AVI was sensitive to the amount of available cognitive resources ( Michail et al, 2021 ). In the current study, the memory loads were different among perceptual-load conditions, showing the highest memory load under high perceptual-load conditions (three attributes) and the lowest memory load under low perceptual-load conditions (one attribute).…”
Section: Discussionmentioning
confidence: 99%